2007
DOI: 10.1097/01.pas.0000249446.28713.53
|View full text |Cite
|
Sign up to set email alerts
|

Fuhrman Grading is not Appropriate for Chromophobe Renal Cell Carcinoma

Abstract: This study was undertaken to assess the prognostic effectiveness of Fuhrman nuclear grading and the individual components of this grading system, in a series of chromophobe renal cell carcinomas. Eighty-seven cases of chromophobe renal cell carcinoma were investigated. There were 47 males and 40 females, 28 to 78 years of age. The carcinomas ranged from 25 to 180 mm in size and on TNM staging there were 38 stage I, 25 stage II, 22 stage III, and 2 stage IV tumors. Whole tumor Fuhrman grading was grade 1, 6 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
97
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 31 publications
2
97
2
3
Order By: Relevance
“…47,48 For papillary RCC it was found that of the three parameters of the Fuhrman system, neither the morphometric measures of nuclear size nor pleomorphism correlated with outcome. Nucleolar prominence, based on the microscopic high-power field showing the greatest degree of nuclear pleomorphism was significantly associated with outcome on univariate analysis, although this was not independent of pT category or TNM stage.…”
Section: Fuhrman Gradingmentioning
confidence: 98%
See 1 more Smart Citation
“…47,48 For papillary RCC it was found that of the three parameters of the Fuhrman system, neither the morphometric measures of nuclear size nor pleomorphism correlated with outcome. Nucleolar prominence, based on the microscopic high-power field showing the greatest degree of nuclear pleomorphism was significantly associated with outcome on univariate analysis, although this was not independent of pT category or TNM stage.…”
Section: Fuhrman Gradingmentioning
confidence: 98%
“…47 For chromophobe RCC not one of the three grading components was correlated with outcome, when tested separately, which raises questions as to the validity of Fuhrman grading for these tumors. 48 Importantly, when tumors in both of these series were classified on the basis of nuclear size alone, utilizing the nuclear diameter cut points proposed by Fuhrman, then all tumors were classified as grade 1, whereas assessment of focal nucleolar prominence on its own showed 58% of papillary RCC and 24% of chromophobe RCC to exhibit grade 3 characteristics.…”
Section: Fuhrman Gradingmentioning
confidence: 99%
“…1 To date, 11 studies tested the ability of FG in prediction of prognosis in chromophobe renal cell carcinoma. [2][3][4][5][6][7][8][9][10][11][12] Seven of those failed to confirm the value of FG. [2][3][4][5][6][7][8] However, all relied on small sample sizes (n ¼ 49-291), thus power may have been insufficient.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] Seven of those failed to confirm the value of FG. [2][3][4][5][6][7][8] However, all relied on small sample sizes (n ¼ 49-291), thus power may have been insufficient. [2][3][4][5][6][7][8] Conversely, four other reported the opposite findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation